FAO‐OIE‐WHO Joint Technical Consultation on Avian Influenza at the Human‐Animal Interface (Influenza Other Respir Viruses, 2010)
Please cite this paper as: Writing Committee for the Joint Technical Consultation on Avian Influenza at the Human‐Animal Interface. FAO‐OIE‐WHO Joint Technical Consultation on Avian Influenza at the Human‐Animal Interface. 7–9 October, 2008, Verona, Italy. Consultation Summary, May 2010. Influenza and Other Respiratory Viruses. 4 (Suppl. 1): 1–29. For the past 10 years, animal health experts and human health experts have been gaining experience in the technical aspects of avian influenza in mostly separate fora. More recently, in 2006, in a meeting of the small WHO Working Group on Influenza Research at the Human Animal Interface (Meeting report available from: http://www.who.int/csr/resources/publications/influenza/WHO_CDS_EPR_GIP_2006_3/en/index.html) in Geneva allowed influenza experts from the animal and public health sectors to discuss together the most recent avian influenza research. Ad hoc bilateral discussions on specific technical issues as well as formal meetings such as the Technical Meeting on HPAI and Human H5N1 Infection (Rome, June, 2007; information available from: http://www.fao.org/avianflu/en/conferences/june2007/index.html) have increasingly brought the sectors together and broadened the understanding of the topics of concern to each sector. The sectors have also recently come together at the broad global level, and have developed a joint strategy document for working together on zoonotic diseases (Joint strategy available from: ftp://ftp.fao.org/docrep/fao/011/ajl37e/ajl37e00.pdf). The 2008 FAO‐OIE‐WHO Joint Technical Consultation on Avian Influenza at the Human Animal Interface described here was the first opportunity for a large group of influenza experts from the animal and public health sectors to gather and discuss purely technical topics of joint interest that exist at the human‐animal interface. During the consultation, three influenza‐specific sessions aimed to (1) identify virological characteristics of avian influenza viruses (AIVs) important for zoonotic and pandemic disease, (2) evaluate the factors affecting evolution and emergence of a pandemic influenza strain and identify existing monitoring systems, and (3) identify modes of transmission and exposure sources for human zoonotic influenza infection (including discussion of specific exposure risks by affected countries). A final session was held to discuss broadening the use of tools and systems to other emerging zoonotic diseases. The meeting was structured as short technical presentations with substantial time available for facilitated discussion, to take advantage of the vast influenza knowledge and experience available from the invited expert participants. Particularly important was the identification of gaps in knowledge that have not yet been filled by either sector. Technical discussions focused on H5N1, but included other potentially zoonotic avian and animal influenza viruses whenever possible. During the consultation, the significant threat posed by subtypes other than H5N1 was continually emphasized in a variety of contexts. It was stressed that epidemiological and virological surveillance for these other viruses should be broadening and strengthened. The important role of live bird markets (LBMs) in amplifying and sustaining AIVs in some countries was also a recurring topic, and the need for better understanding of the role of LBMs in human zoonotic exposure and infection was noted. Much is understood about the contribution of various virus mutations and gene combinations to transmissibility, infectivity, and pathogenicity, although it was agreed that the specific constellation of gene types and mutations that would characterize a potentially pandemic virus remains unclear. The question of why only certain humans have become infected with H5N1 in the face of massive exposure in some communities was frequently raised during discussion of human exposure risks. It was suggested that individual‐level factors may play a role. More research is needed to address this as well as questions of mode of transmission, behaviors associated with increased risk, virological and ecological aspects, and viral persistence in the environment in order to better elucidate specific human exposure risks. It became clear that great strides have been made in recent years in collaboration between the animal health and public health sectors, especially at the global level. In some countries outbreaks of H5N1 are being investigated jointly. Even greater transparency, cooperation, and information and materials exchange would allow more timely and effective responses in emergency situations, as well as in assessment and planning phases. Ensuring sustainability was also frequently emphasized, e.g. in infrastructure and capacity development and in development of tools and systems for surveillance, assessment and response. It was suggested that one way for tools and systems built or planned to address avian influenza to become more sustainable would be to make them applicable for a broader array of existing and emerging zoonotic diseases.